Собор без крестов - 2 - Шитов Владимир (Детектив. Триллер. Политика, 1996)
Экземпляры: ф.2 (20100914) / Инвентарный номер: 96173 / Цена: 35 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 64 / ББК: 84(2Рос=Рус)6